Teaching Procedural Texts: An Eco-Linguistics Perspective - Mochamad Rizqi Adhi Pratama; Maya Kurnia Dewi; Tommi Yuniawan (RETORIKA: Jurnal Ilmu Bahasa, 2020)
The Curriculum 2013expects the students to possess both academic achievement and noble characters. Environmental awareness is one of noble characters proposed by The Curriculum 2013that relates to the eco-linguistics as an interdisciplinary science which involves ecology and linguistics. The objective of this study is to examine the effectiveness of teaching text in the light of eco-linguistics perspective to teach procedural text and recycling garbage. This study employed a mixed method research design. The quantitative method (one group pretest-posttest design of pre-experimental research) is concerned with the improvement assessment of writing procedural text while the qualitative one (questionnaire) was dealt with the investigation of students’ knowledge and response about recycling garbage. The research subjects were one class of Junior High School consisting of 32 students taken by purposing sampling. A scoring system of assessing writing proposed by The Curriculum 2013was used in this study. While the instrument to assess the students’ knowledge and response to recycling garbage, a closed question type of questionnaire was applied. The results showed that there is a significant improvement in students writing from 76,72 (pre-test) to 80,47 (post-test). The results of questionnaire also revealed that the students positively respond to the conducted teaching and they have learnt recycling garbage.